Places that created time in the Danube Gorges and beyond, c. 9000-5500 BC - Borić, Dušan (Documenta Praehistorica, 1999)
The history of the region of the central Balkans and south east Pannonia is reviewed over the period of c. 9000-5500 cal BC. The rich and exciting evidence of the Danube Gorges region (the Djerdap) is presented in relation tothe ecological setting nad Early/Middle neolithoc settlement evidence of the wider region. It is suggested that the nature of these first Neolithic societies itself provides answers to the question of their origins, despite the recurrent invisibility of extensive Masolithic occupation in Southeast Europe as a whole.
Keywords: neolitik; mezolitik; Djerdap; naselbine; ceramic; keramika; archaeology; arheologija; arheološke najdbe